Estudo de adoção da ETE descentralizada de Porto Cubatão (Cananéia-SP) - Nakazawa, Emerson Khin Pereira (Universidade Federal de São Carlos, 2024)
With the promulgation of Federal Law No. 14,026/2020, which changes the Legal Framework for Basic Sanitation, and the new goal of universalizing the basic sanitation system, populations increasingly distant from urban centers must be covered by the collection and treatment of sewage, however the inclusion of this portion of the population introduces new challenges, because they are located far from existing networks, it may not be viable to interconnect these collection points. Decentralized ETEs are one of the solutions used, as they have a lower implementation cost, smaller occupation area in these more isolated areas, and high efficiency in removing quality parameters, as can be seen through the data made available by the concessionaire in the region studied. Ribeira Valley.
Study of the implementation of the decentralized ETE in Porto Cubatão (Cananéia-SP)
Keywords: ETE descentralizada; Marco regulatório do saneamento básico; Vale do ribeira; Wastewater treatment; Ribeira valey; universalizing the basic sanitation system; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO